ANALISA KELAYAKAN PEMBANGUNAN FLYOVER DI BUNDARAN DOLOG KOTA SURABAYA - Rahman, Rahmatang (MEKTEK, 2010)
The congestion of traffic stream resulting in increased vehicle operating costs and the loss a lot of time forusers. Fuel compsumption will increase and will indirectly increase air pollution due to exhaust emissionsfrom vehicle traffic. Overall congestion caused inconveniens for road users.Flyover at Bundaran Dolog designed to solve the problem of congestion in Bundaran Dolog caused byconflict of traffic movement between Jalan Ahmad Yani that serves as a primary arterial road with JalanJemursari that serves as primary arterial road and a crossing with the railway track in the side east JalanAhmad Yani. LHR Volume forecast made during the life of the plan was first opened to vehicle traffic in2009, ie until the year 2009. Flyover design plans in Bundaran Dolog taken from the Final EvaluationReport Detailed Spatial Plan Area Siwalankerto 2006. Flyover plan this age 20 years olad, which is assumedto be done for development in 2008 and opened to traffic in 2009. Planned each direction of motion consistsof 2 lines, so that reporting requirements per lane ROW per direction of motion is about 10 meters.Based on the results of that analysis, feasibility analysis of development in Bundaran Dolog flyovereconomically feasible. It can be seen from the value NPV= Rp. 177,974,154,514.15 and BCR= 1.99